Genetic Overlap Between Antipsychotic Response and Susceptibility to Schizophrenia. Issue 1 (February 2015) - Ikeda, Masashi; Yoshimura, Reiji; Hashimoto, Ryota; Kondo, Kenji; Saito, Takeo; Shimasaki, Ayu; Ohi, Kazutaka; Tochigi, Mamoru; Kawamura, Yoshiya; Nishida, Nao; Miyagawa, Taku; Sasaki, Tsukasa; et al.
Abstract : Supplemental digital content is available in the text.